Time dependent reduction in platelet aggregation using the multiplate analyser and hirudin blood due to platelet clumping - Kent Chapman; Emmanuel J. Favaloro (Platelets, 2018)
The Multiplate is a popular instrument that measures platelet function using whole blood. Potentially considered a point of care instrument, it is also used by hemostasis laboratories. The instrument is usually utilized to assess antiplatelet medication or as a screen of platelet function. According to the manufacturer, testing should be performed within 0.5–3 hours of blood collection, and preferably using manufacturer provided hirudin tubes. We report time-associated reduction in platelet aggregation using the Multiplate and hirudin blood collection tubes, for all the major employed agonists. Blood for Multiplate analysis was collected into manufacturer supplied hirudin tubes, and 21 consecutive samples assessed using manufacturer supplied agonists (ADP, arachidonic acid, TRAP, collagen and ristocetin), at several time-points post-sample collection within the recommended test time period. Blood was also collected into EDTA as a reference method for platelet counts, with samples collected into sodium citrate and hirudin used for comparative counts. All platelet agonists showed a diminution of response with time. Depending on the agonist, the reduction caused 5–20% and 22–47% of responses initially in the normal reference range to fall below the reference range at 120min and 180min, respectively. Considering any agonist, 35% and 67% of initially “normal” responses became ‘abnormal’ at 120 min and 180 min, respectively. Platelet counts showed generally minimal changes in EDTA blood, but were markedly reduced over time in both citrate and hirudin blood, with up to 40% and 60% reduction, respectively, at 240 min. The presence of platelet clumping (micro-aggregate formation) was also observed in a time dependent manner, especially for hirudin. In conclusion, considering any platelet agonist, around two-thirds of samples can, within the recommended 0.5–3 hour testing window post-blood collection, yield a reduction in platelet aggregation that may lead to a change in interpretation (i.e., normal to reduced). Thus, the stability of Multiplate testing can more realistically be considered as being between 30–120 min of blood collection for samples collected into hirudin.